KEGIATAN EDUKATIF “TIM AKSI BERGIZI” PADA REMAJA DI KABUPATEN TUBAN - Mohammad Zainul Ma'arif; Idcha Kusma Ristanti; Dian Ayu Ainun Nafies (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2021)
Nutritional problems in adolescents are increasingly complex due to limited knowledge about balanced nutrition in adolescents. The increasing number of dual nutritional problems, especially in adolescents in Tuban Regency. The Nutrition Action Team is one form of nutrition education efforts to reduce nutritional problems in adolescents. This community service activity is carried out for high school students in Tuban Regency. In the Nutrition Action Team activities, all participants were able to understand well about nutrition in the life cycle of adolescents, adolescent nutrition problems, 10 messages of balanced nutrition. It is hoped that in the future this community service activity can be carried out in a sustainable manner, so as to create a positive attitude towards nutrition, the formation of knowledge and skills in choosing and using food sources, the emergence of good eating habits and the motivation to find out more about matters related to nutrition.